GROSS ANATOMY AND HISTOMORPHOLOGY OF TESTES IN NEW ZEALAND WHITE RABBIT - Emmanuel B Farayola; Adenike O; Olatunji-Akioye (Exploratory Animal and Medical Research, 2020)
The present study investigated the gross and histological description of the rabbit testes with the histomorphometrical indices of the testes. Four male intact New Zealand white rabbits were procured with average weight of 1.35 ±0.13kg and were housed in individual cages at the animal house of the Faculty of Veterinary Medicine, University of Ibadan. Gross pictures and measurements of the testes were recorded while the testes tissues were processed for histology and histometric assessment of seminiferous tubules. Results showed that gross measurement of the right testis were about 2.88cm in length and 0.61cm in breadth. The measurement of the left testis were about 2.65cm and 0.65cm. The average histomorphometrical readings for the seminiferous tubular diameter and seminiferous epithelial height were 265.84µm and 204.09µm respectively. The histological slides revealed normal testicular architecture in the rabbits.